(untitled) (University Journal of Zoology, Rajshahi University, 2012)
The insecticidal and repellent activity tests of the chloroform extracts of fruit, leaf, root and stem of Urena sinuata L. against the red flour beetle Tribolium castaneum L. adults have been conducted. The leaf, root and stem extracts showed high toxicity by giving mortality of the beetles within 30 min. of exposure. The LD50 values for the 12, 24, 36 and 48h of exposures were 0.354, 0.262, 0.209 and 0.196mg cm2 for the fruit extract; 0.587, 0.413, 0.355 and 0.299mg cm2 for the leaf extract; 0.440, 0.389, 0.340 and 0.268mg cm2 for the root extract and 0.968, 0.661, 0.491 and 0.362mg cm2 for the stem extract. The insecticidal activity can be arranged in the order of fruit> root> leaf> stem extracts. The root and stem showed repellent activity against T. castaneum adults at P<0.01 and P<0.05 levels of significance, while the fruit and the leaf extracts did not show repellency at all. DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10740 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 25-28